2005
DOI: 10.1177/1468797605066924
|View full text |Cite
|
Sign up to set email alerts
|

Tourism translations

Abstract: This article discusses Actor–Network Theory (ANT) and its utility for tourism studies. It argues that ANT can be an effective methodological approach for studying tourism development due to two reasons. First, its ability to deal with relational materiality of the social world, immanent in the concept of translation which highlights the net- workpractices of different actors; and second, its willingness to grasp multiple relational orderings, thus drawing diverse forms of tourism spatiality into analysis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(49 citation statements)
references
References 29 publications
0
41
0
5
Order By: Relevance
“…This innovative approach opens up new conceptual and methodological perspectives for tourist studies (Jóhannesson, 2005), but has as yet been rarely, and mostly only recently, introduced into tourism research (Valkonen, 2010;van der Duim, 2007;van der Duim, Ren, & Jóhannesson, 2012). Paget et al (2010) have used ANT in a study of a successful innovative project in a French ski resort; Ren (2011, p. 858) sought to demonstrate, by the use of ANT, how "a rather unlikely [non-human] destination actor, the [polish] oscypek cheese, is enacted in different versions as it engages with tourism, tradition, craftsmanship, hygiene and legislation;" Gren and Huijbens (2012) deployed it in their paper intended to re-introduce the Earth into tourism theory; Rodger, Moore and Newsome (2009) used it to examine the sciencewildlife tourism interface, and John Tribe (2010) used it to analyze the International Academy for the Study of Tourism (IAST).…”
Section: Actor-network Theorymentioning
confidence: 99%
“…This innovative approach opens up new conceptual and methodological perspectives for tourist studies (Jóhannesson, 2005), but has as yet been rarely, and mostly only recently, introduced into tourism research (Valkonen, 2010;van der Duim, 2007;van der Duim, Ren, & Jóhannesson, 2012). Paget et al (2010) have used ANT in a study of a successful innovative project in a French ski resort; Ren (2011, p. 858) sought to demonstrate, by the use of ANT, how "a rather unlikely [non-human] destination actor, the [polish] oscypek cheese, is enacted in different versions as it engages with tourism, tradition, craftsmanship, hygiene and legislation;" Gren and Huijbens (2012) deployed it in their paper intended to re-introduce the Earth into tourism theory; Rodger, Moore and Newsome (2009) used it to examine the sciencewildlife tourism interface, and John Tribe (2010) used it to analyze the International Academy for the Study of Tourism (IAST).…”
Section: Actor-network Theorymentioning
confidence: 99%
“…By a relational approach, rhetorically acknowledged by the European union as important (EC, 2005(EC, , 2011a, we intend to address a 'lack of standing for non-positivistic environmental studies' (Hall, 2013, p. 12). In tourism research, a number of actor-network theory studies have identified this lack and dealt with it by taking a symmetrical approach to human and non-human actants (Franklin, 2004;Gren and Huijbens, 2012;J ohannesson, 2005;Paget et al, 2010;Rodger et al, 2009;van der Duim, 2007;van der Duim et al, 2013). Drawing upon this 'material turn' in the social sciences with specific reference to environmental issues (cf.…”
Section: A Market Theorization Of Sustainable Developmentmentioning
confidence: 97%
“…: HAMMERICH, 2003;MALCOM;MANSFIELD, 2013), cultura e turismo são exemplos da relevância do papel da sociologia nos estudos turísticos. Na esteira das contribuições já mencionadas, neste estudo adotamos como referência sociológica uma epistemologia da prática social (RECKVITZ, 2002;NICOLINI, 2013;BISPO, 2016a;2016b), já considerada por alguns autores do turismo por meio da Teoria Ator-Rede (TAR), a exemplo de Edensor (2001), Jóhannesson (2005), Cohen e Cohen (2012) e Duim (2007. Edensor (2001, p. 60) aborda o turismo na perspectiva do paradigma da performatividade, considerando-o um fenômeno social a partir do qual atores podem interagir.…”
Section: Abordagens Sociológicas Do Turismo -Convergindo Para O Campounclassified
“…Entretanto, Cohen e Cohen (2012), assim como Jóhannesson (2005), não trazem o conceito de prática ao tratar da TAR nos seus trabalhos.…”
Section: Abordagens Sociológicas Do Turismo -Convergindo Para O Campounclassified
See 1 more Smart Citation